2016
DOI: 10.1002/nau.23009
|View full text |Cite
|
Sign up to set email alerts
|

Intradetrusor injections of onabotulinum toxin A (Botox®) 300 U or 200 U versus abobotulinum toxin A (Dysport®) 750 U in the management of neurogenic detrusor overactivity: A case control study

Abstract: Intradetrusor injections of abobotulinum toxin 750 U for NDO provided better outcomes than injections of onabotulinum toxin 200 U. Success rates of abobotulinum toxin 750 U and onabotulinum toxin 300 U were similar but interval between injections tended to be longer with onabotulinum toxin 300 U. Neurourol. Urodynam. 36:734-739, 2017. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…In another animal model study, Oliveira et al found that OTA was 1.6 times more potent than ATA . Another recent study proposed a ratio between 1:2.5 and 1:3.75 in the human neurogenic bladder, as 750 U ATA were found to be more efficacious than 200 U OTA, but not more efficacious than 300 U OTA . As the controversy of the dose‐equivalence between the two toxins remains unsolved, it has been suggested that a difference in dose equivalence could explain the good results obtained with BTA switch.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another animal model study, Oliveira et al found that OTA was 1.6 times more potent than ATA . Another recent study proposed a ratio between 1:2.5 and 1:3.75 in the human neurogenic bladder, as 750 U ATA were found to be more efficacious than 200 U OTA, but not more efficacious than 300 U OTA . As the controversy of the dose‐equivalence between the two toxins remains unsolved, it has been suggested that a difference in dose equivalence could explain the good results obtained with BTA switch.…”
Section: Discussionmentioning
confidence: 99%
“…27 Another recent study proposed a ratio between 1:2.5 and 1:3.75 in the human neurogenic bladder, as 750 U ATA were found to be more efficacious than 200 U OTA, but not more efficacious than 300 U OTA. 29 As the controversy of the dose-equivalence between the two toxins remains unsolved, 21,22 it has been suggested that a difference in dose equivalence could explain the good results obtained with BTA switch. The association between dose of ATA injected and success of the toxin switch observed in our study supports | 295 this latter hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…14 The results of ABO injections for managing the OAB/ DO are comparable to those from ONA. 18,19,21,25 Most trials reporting ABO injections in neurogenic OAB have considered 500 U as the starting dose. 17 [18][19][20] Better results using higher doses of ABO were observed.…”
Section: Discussionmentioning
confidence: 99%
“…In urology, onabotulinumtoxinA and abobotulinumtoxinA are the two most commonly used formulations, the first one being the only licensed one in the USA and Europe for NDO and IDO management . However, randomized clinical trials support the use of ABO for NDO, and small uncontrolled studies have reported its use in IDO/OAB …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation